2017
DOI: 10.1111/1748-5967.12207
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic effects on the distributions of major insect species in agricultural fields

Abstract: We compared how abiotic factors affect the regional distributions of four insect groups (Dermaptera, Formicidae, Orthoptera and Diptera). Insects were collected using a pitfall trap from 36 agricultural field sites, and 31 933 individuals encompassing 139 species were observed. The distribution pattern of dominant species was not obviously different among the four groups. Species richness (H′) of Orthoptera showed a negative and positive correlation with precipitation and sunlight duration, respectively. Longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Higher abundance of Diptera in pasture monocultures has been reported previously 42 , 43 . Composition of Orthoptera communities is known to be greatly affected by plant cover 44 and changes of environmental conditions, forming distinct communities characteristic of areas with low vegetational cover and others characteristic of high vegetation cover 45 47 . Some studies have reported that abundance of some groups falls with habitat simplification 48 , while in other groups abundance increases 49 which was also recorded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher abundance of Diptera in pasture monocultures has been reported previously 42 , 43 . Composition of Orthoptera communities is known to be greatly affected by plant cover 44 and changes of environmental conditions, forming distinct communities characteristic of areas with low vegetational cover and others characteristic of high vegetation cover 45 47 . Some studies have reported that abundance of some groups falls with habitat simplification 48 , while in other groups abundance increases 49 which was also recorded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed that climatic changes strongly affect the abundance and geographical distribution of orthopteran insects. (Eo et al, 2017, Weiss et al, 2012. Due to their sensitivity to microclimate, orthopteran species are considered as biological indicators.…”
Section: Introductionmentioning
confidence: 99%